2007
DOI: 10.1007/s10812-007-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence excitation spectra of jet-cooled carbazole complexes with monohydric alcohols

Abstract: We have analyzed the fluorescence excitation spectra of carbazole complexes with a single molecule of methyl, deuterated methyl, ethyl, and propyl (1-propanol and 2-propanol) alcohols, cooled in a supersonic jet. We have determined the shifts in the fluorescence excitation spectra of the complexes relative to the frequency of the purely electronic transition of unbound carbazole. They occur as a result of formation of hydrogen bonds between the N-H group of the carbazole and the OH group of the alcohols. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Among these studies, several complexes involving heteroaromatic moieties are found including works on indole-water, 10 7-azaindole-water, 11 pyrrole- 12 and carbazole-solvent complexes. 13,14 Moreover, several studies on furan derivatives were carried out, including a comparative FTIR jet and theoretical study on 2,5-dimethylfuran-as well as the 2,3-benzofuran-methanol complexes. 15 The latter have additionally been studied by laser induced fluorescence and IR fluorescence dip spectroscopy, including the respective water complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, several complexes involving heteroaromatic moieties are found including works on indole-water, 10 7-azaindole-water, 11 pyrrole- 12 and carbazole-solvent complexes. 13,14 Moreover, several studies on furan derivatives were carried out, including a comparative FTIR jet and theoretical study on 2,5-dimethylfuran-as well as the 2,3-benzofuran-methanol complexes. 15 The latter have additionally been studied by laser induced fluorescence and IR fluorescence dip spectroscopy, including the respective water complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The non-classical hydrogen bond, interaction between an H atom (bound to one of the electronegative C, O, or N atoms) and the π-electron cloud of an aromatic ring, has been widely studied in the last decade. Such weak non-covalent bonds are formed intramolecularly [1-3] or intermolecularly [4,5] in van-der-Waals complexes in biological systems. Weak H-bonds should be considered when examining molecular structures of fluxional molecules and their stabilization energies.…”
mentioning
confidence: 99%